DEVELOPMENT OF MODERN MEASURES TO IMPROVE MICROCLIMATIC PARAMETERS AT INDUSTRIAL ENTERPRISES - Tohirov Aziz Avaz Ugli; Rasulev Aliakbar Khamidullaevich (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Meteorological conditions in industrial premises, or their microclimate, depend on the thermophysical characteristics of the technological process, climate, season of the year, ventilation and heating conditions. The microclimate of industrial premises is understood as the climate of the internal environment of these premises surrounding a person, which is determined by the combinations of temperature, humidity and air velocity acting on the human body, as well as the temperature of the surrounding surfaces.